If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 10 + x = -2 + -1x Reorder the terms: 10 + x + x = -2 + -1x Combine like terms: x + x = 2x 10 + 2x = -2 + -1x Solving 10 + 2x = -2 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 10 + 2x + x = -2 + -1x + x Combine like terms: 2x + x = 3x 10 + 3x = -2 + -1x + x Combine like terms: -1x + x = 0 10 + 3x = -2 + 0 10 + 3x = -2 Add '-10' to each side of the equation. 10 + -10 + 3x = -2 + -10 Combine like terms: 10 + -10 = 0 0 + 3x = -2 + -10 3x = -2 + -10 Combine like terms: -2 + -10 = -12 3x = -12 Divide each side by '3'. x = -4 Simplifying x = -4
| 4x+3=5x+2 | | -9-8x=-9x+16 | | -3(8-4x)=4(x+2) | | ax^2+b=c | | -5x-45=-9x+67 | | A+bi=13+7i | | -3x-27=-6x+27 | | 9x-99+8x-36=86 | | u+41=v+48 | | 2x+y=11(1) | | n-2-7=-(6n-5)-5(n-2) | | 16.3+s=36.94 | | x^5-6x^2+9x-3=0 | | x^5-6x^2+9x-3=0 | | x^5-6x^2+9x-3=0 | | 15-9d-4d=5-3d | | x^5-6x^2+9x-3=0 | | 4.0p+14.10=4.50(p+3) | | 7x+9=90 | | 15-9d-4d=5-3d | | 3-17x=-31 | | 16.3+s=36.94 | | n-2-7=-(6n-5)-5(n-2) | | 4.0p+14.10=4.50(p+3) | | n-2-7=-(6n-5)-5(n-2) | | 7x+9=90 | | 3x-9+(x+7)=90 | | X=12-y | | n-2-7=-6(6n-5)-5(n-2) | | 150=x(60) | | 5x-22+(4x+4)=90 | | .75a=14.25 |